RISK ASSESSMENT ON INSTALL AND DISMANTLE SCAFFOLDING USING TASK RISK ASSESSMENT METHOD - Azura, Talitha Cornelia; Ashari, Moch. Luqman; Sandora, Rina (Tibuana, 2019)
Accidents can occur anytime and anywhere such as accidents that occur at work at height. This study aims to identify and analyze potential hazards in the install and dismantle scaffolding work using TRA (Task Risk Assessment) method. The results of the risk assessment using TRA on this work obtained four job description with 2 jobs at low risk, namely initial risk of 4 and after controlling for residual risk of 2. For install and dismantle scaffolding show that medium risk was obtained with an initial risk of 12 and after controlling, the residual risk becomes 9.